Pengembangan Bahan Ajar Mata Kuliah Konsep Dasar Bahasa dan Sastra Indonesia Berbasis Kontekstual STKIP PGRI Lubuklinggau - Sri Murti; Dian Ramadan Lazuardi (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2019)
This study aims to determine the design of instructional materials development, validation results, and effectiveness of the use of contextual basic concepts of indonesian language and literature in STKIP PGRI Lubuklinggau students. This research uses the R&D (research and development) approach of the Borg and Gall model. The steps of development that researchers do namely, preliminary research, planning development models, validation, evaluation, and revision of the model. Furthermore, teaching material products are tested on students with the steps: 1) Portotype testing, 2) Initial input, 3) Small group testing, 4) Field testing. Based on the results of the validation of three experts regarding the teaching materials of the basic concepts of indonesian language and literature, the results obtained by 80%, the teaching materials are in good category. The results of this study also showed that contextual based indonesian conceptual language and literature teaching materials were effectively used in lectures. Keywords: Teaching Materials, Contextual, Basic Concepts